Relationships between emotional intelligence, emotional creativity and values: sex differences in early adult - Andreyeva, Iryna N. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article reflects the results of a study of gender differences in the relationship of emotional intelligence and emotional creativity with values in early adulthood. Significant positive relationships common to individuals of both sexes were revealed: interpersonal emotional intelligence, ability to understand emotions with the value of independence, ability to manage emotions with the value of tradition, preparedness with the value of independence. The relationship of authenticity with the value of achievement is positive for women and negative for men. A number of correlations of emotional intelligence and emotional creativity with values, specific for male and female samples, have been established. The scientific novelty lies in the fact that for the first-time data have been obtained on the relationship of emotional intelligence and emotional creativity with values in the period of early adulthood.
Keywords: reflective emotional intelligence; interpersonal and intrapersonal emotional intelligence; reflective emotional creativity; values